Hubungan Antara Orientasi Masa Depan Dengan Kesiapan Kerja Siswa SMK - Afra Nafisah, Sausan; , Susatyo yuwono.,S.Psi,.M.Si,.Psi (2017)
The open unemployment rate of the population is dominated by SMK graduates with a percentage of 12.65%. This happens because of the gap between the needs of the world of work with the provision of labor from vocational education institutions. Based on these data shows the low absorption of SMK graduates in the world of work. One reason is the lack of readiness of vocational students in business and industry. This study aims to determine the correlation between future orientation with the job readiness of vocational high school students. Hypothesis proposed that there is a positive correlation between future orientation with the job readiness of vocational high school students. Subjects in this study amounted to 154, which is the seventh grade students of SMK Muhamadiyah 6 Tirtomoyo. The sampling technique conducted in this study is population study. Methods of data collection using a quantitative approach with a measure of future orientation scale and job readiness scale. While data analysis is done by product moment correlation analysis using SPSS for 16 windows help program. Based on the results of data analysis obtained correlation coefficient of 0.657; Significance (p) of 0.000 (p <0.01) which means to a very significant positive correlation between the future orientation with the job readiness of vocational high school students. Effective contribution or the role of future orientation to job readiness of 43.2%, the remaining 56.8% influenced by other factors. Work preparedness variable has empirical mean (RE) equal to 116,79 so that have category which is classified, meanwhile future orientation variable has empirik mean (RE) equal to 102,38 which have high category. Keyword : Future orientation, Job readiness, Vocational high school students